2015
DOI: 10.1111/sjop.12254
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about intimate partner violence: A survey of the Swedish general public

Abstract: Public interventions are considered to be an important means of preventing intimate partner violence (IPV). What people believe about the nature of IPV is likely to determine their propensity to intervene, but little is known at present about IPV beliefs among the general public. In a survey of 650 Swedish citizens, beliefs about the prevalence and causes of IPV, and viable means of intervention were assessed. Respondents estimated, on average, that IPV occurs in almost one quarter of all intimate relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 56 publications
(93 reference statements)
1
21
0
4
Order By: Relevance
“…Men scored higher than women on the JPV and VRV subscales, whereas women scored higher on the ARV subscale. These results agree with other research indicating that women tend to attribute less responsibility to the victims of IPV and more blame to the perpetrators than men (Alfredsson et al, 2016;Valor-Segura et al, 2011). Our results also revealed that women's beliefs about justification of IPV and victims' responsibility for IPV were similar in all age groups whereas men tended to take a more tolerant approach to IPV and be more lenient towards the perpetrators if they were over 50 years old.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Men scored higher than women on the JPV and VRV subscales, whereas women scored higher on the ARV subscale. These results agree with other research indicating that women tend to attribute less responsibility to the victims of IPV and more blame to the perpetrators than men (Alfredsson et al, 2016;Valor-Segura et al, 2011). Our results also revealed that women's beliefs about justification of IPV and victims' responsibility for IPV were similar in all age groups whereas men tended to take a more tolerant approach to IPV and be more lenient towards the perpetrators if they were over 50 years old.…”
Section: Discussionsupporting
confidence: 82%
“…For example, women tend to express stronger disapproval of IPV (Sakalli, 2001) and to hold more lenient attitudes toward IPV victims than men (Alfredsson, Ask, & Borgstede, 2016;LanghinrichsenRohling, Shlien-Dellinger, Huss, & Kramer, 2004) whereas men are more likely to agree with myths about IPV (Ferrer et al, 2006;Flood & Pease, 2009) and tend to excuse the abuser's aggressive behaviour and blame victim more than women (Valor-Segura, Expósito, & Moya, 2008;.…”
Section: Attitudes To and Beliefs About Ipvmentioning
confidence: 99%
“…Not only is there denial of its existence as a phenomenon but also reasons are found to justify the aggression (for example, previous insults, infidelity, going out without permission, etc.) along with blaming the victim for not putting a stop to such abuse and violent actions [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of the research conducted on citizens’ attitudes towards VAW has focused on issues such as the subjective definition of this type of violence, its acceptance and tolerance, the blaming of victims, and the predisposition to report it. However, as Alfredsson et al (2016) pointed out, we know relatively little regarding people’s beliefs about the prevalence of VAW in our societies. In order to help fill this knowledge gap, the current investigation examines the perceptions of women living in Europe regarding the magnitude of VAW in their country of residence and explanatory factors.…”
Section: Introductionmentioning
confidence: 99%